(3QSGdI aj EKHGJ GdhGLHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3cd TF ai YGde Gdchf hGdaSGO eeG de jcf acGf bHd Gdchf eecf GdhLhO cGf eeJfY GdhLhO deG hLOfG dh cGf hGLH GdhLhO dcGf dc jRd hdG jRGd ehLhOkG s
(3BNQgG (B:s
(3hGTQa GdfGS ai gPG GdYGde ef cGfJ faSg GdfWbjI YbdGA HGdaYd hCTQa ef cGfJ faSg GdefWbjI YbdGA HGdaYd ef dg GdfaS GdbOSjI GdfHhjI JeJ GdQSGdI hddg GdMeO dG fgGjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds